2014
DOI: 10.1017/erm.2014.14
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted therapies for acute kidney injury

Abstract: Acute kidney injury (AKI) is a serious clinical condition with no effective treatment. Tubular cells are key targets in AKI. Tubular cells and, specifically, proximal tubular cells are extremely rich in mitochondria and mitochondrial changes had long been known to be a feature of AKI. However, only recent advances in understanding the molecules involved in mitochondria biogenesis and dynamics and the availability of mitochondria-targeted drugs has allowed the exploration of the specific role of mitochondria in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 149 publications
(227 reference statements)
2
86
0
1
Order By: Relevance
“…38,39 Molecules generated within injured cells have also been recently identified as potential targets to abrogate inflammation. 40 For example, the cysteine proteases (calpains and caspases) play a role in hypoxia-induced injury in proximal tubular cells, and mitochondrial mediators are gaining interest as potential antiinflammatory targets in several cell types. Inhibitors of mitochondrial permeability transition pore opening, quinone analogs, superoxide dismutase mimetics, SzetoSchiller peptides, and mitochondrial division inhibitors have already shown promise in diverse models of AKI, and Figure 2.…”
Section: Basic Concepts Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Molecules generated within injured cells have also been recently identified as potential targets to abrogate inflammation. 40 For example, the cysteine proteases (calpains and caspases) play a role in hypoxia-induced injury in proximal tubular cells, and mitochondrial mediators are gaining interest as potential antiinflammatory targets in several cell types. Inhibitors of mitochondrial permeability transition pore opening, quinone analogs, superoxide dismutase mimetics, SzetoSchiller peptides, and mitochondrial division inhibitors have already shown promise in diverse models of AKI, and Figure 2.…”
Section: Basic Concepts Of Inflammationmentioning
confidence: 99%
“…40 Finally, microRNAs generated in injured renal tubular cells are also gaining interest as potential targets. 41,42 In summary, a large and rapidly expanding array of inflammatory cell types and molecular mediators has been implicated in the pathogenesis of AKI, and data from rodent models have clearly shown that deletion, blockade, or enhancement of many of these can improve experimental outcomes.…”
Section: Basic Concepts Of Inflammationmentioning
confidence: 99%
“…Renal IRI often occurs in partial nephrectomy, renal transplantation and various urological vascular surgeries that may transiently reduce renal blood flow [7]. Renal IRI is a risk for acute renal failure and delayed graft function clinically [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the following sections, consideration will be given to the respective merits of each of these approaches. As this article is focused on strategies currently in vogue, older targets will not be discussed, such as inhibitors of the mitochondrial permeability transition pore, which have been covered in depth elsewhere [11].…”
Section: Mitochondrial-targeted Therapiesmentioning
confidence: 99%